Life history effects of prey choice by copepods: implications for biocontrol of vector mosquitoes - Dieng, Hamady; Boots, Michael; Tuno, Nobuko; Tsuda, Yoshio; Takagi, Masahiro (The American Mosquito Control Association, 2003)
Macrocyclops distinctus, Megacyclops viridis, and Mesocyclops pehpeiensis, which are common in rice fields during the summer season in Nagasaki, Japan, showed variable potentialities as biological control agents of larval Aedes albopictus, Culex tritaeniorhynchus, and Anopheles minimus in the laboratory. Macrocyclops distinctus and M. viridis, the largest copepod species, had fewer eggs within an egg clutch in nature than the smallest species, M. pehpeiensis, which also had a lower developmental time for sexual maturation (based on the appearance of the 1st clutch). Longevity as well as fecundity were influenced by nutritional conditions and varied significantly between the species. All species had shorter life spans when starved, but resistance to starvation was more pronounced in the larger species. All the species had lower clutch production when starved. Also, although the frequency of clutch production was high in M. pehpeiensis (M. pehpeiensis produced a clutch every 2 days, whereas M. distinctus and M. viridis took on average almost 3 days), total clutch production was far higher in the larger species. The copepods fed readily on mosquito larvae, with M. distinctus and M. viridis killing fewer Ae. albopictus than M. pehpeiensis, which, however, killed fewer An. minimus. These copepods exhibited a similar and limited predation against Cx. tritaeniorhynchus. Results of our study support the contention that these copepods have the potential to be used as biological control agents of immature mosquitoes. Also, our results give useful information on colony maintenance and field introduction. In particular, releasing copepods with Paramecium as food could increase their survival in the habitat of the targeted pest.